PSYCHOLOGICAL EFFECTS AND ANALYSIS OF CHILDREN OF STUDY THEFT IN JAKARTA SOCIAL INSTITUTIONS - Cindy Aprilia Chandra; Fakhri Dhiya Hidayat (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Theft is a crime that is intended for property and goods and often occurs in society. This crime is an action that can shake the security stability of both the assets and the lives of citizens. Therefore, the Criminal Code (KUHP) emphasizes detailed and severe punishment for violators. This can be seen from the form of punishment and the threat of punishment imposed(Arief Rahman Kurniadi 2022: h.77). Theft is also a criminal act, if it is committed by an adult, he will undergo a legal process, but in general, if he is caught, he must go through the legal process that has been in effect. But it is different if the crime of theft is committed by children, and of course the legal process that is enforced is also different(Usep Tatang Suryadi and Yana Supriatna 2019: h.15).